2003
DOI: 10.2176/nmc.43.301
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm of the Distal Posterior Inferior Cerebellar Artery Originating from the Extracranial and Extradural Vertebral Artery-Case Report-

Abstract: A 42-year-old woman presented with a ruptured aneurysm of the distal posterior inferior cerebellar artery (PICA), which had a rare extracranial and extradural origin. Medial suboccipital craniectomy and C-1 laminectomy were performed. The aneurysm had adhered to the right cerebellar tonsil, but was successfully clipped without difficulty. Intraoperatively, the PICA origin was recognized in the extracranial and extradural space between the dorsal roots of the C-1 and C-2 nerves. The origin of the PICA from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…15 -30 % of all PICA aneurysms are seen in the distal part and especially in the peripheral PICA segments [2] . Although in some series, the distal segment PICA aneurysm incidence is higher in the telovelotonsillar and tonsillomedullar segments [1] , it is reported that, in a 16-case-series which comprises 18 aneurysms, the incidence is higher in the anterior medullar segment [11] . It is thought that hemodynamic stress and congenital factors play role in the occurrence of distal PICA aneurysms [12] .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…15 -30 % of all PICA aneurysms are seen in the distal part and especially in the peripheral PICA segments [2] . Although in some series, the distal segment PICA aneurysm incidence is higher in the telovelotonsillar and tonsillomedullar segments [1] , it is reported that, in a 16-case-series which comprises 18 aneurysms, the incidence is higher in the anterior medullar segment [11] . It is thought that hemodynamic stress and congenital factors play role in the occurrence of distal PICA aneurysms [12] .…”
Section: Discussionmentioning
confidence: 90%
“…Distal PICA aneurysms are particularly rare. It is reported that their observation rate is about 0.28 -1.4 % among all cerebral aneurysms [1] . The VA-originated aneurysms appear in the PICA in 80 % and usually in the VA-PICA division point.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors described the existence of PICAs originating from V 3 in case reports, and the incidence of these PICAs was estimated based on cadaveric inspection in Western countries. 2,6,10,13,15,20,24,[29][30][31] However, the clinical utility of using enhanced CT scans as a diagnostic tool has not been evaluated. In the present study, we analyzed Japanese patients who underwent contrast CT examination.…”
Section: Discussionmentioning
confidence: 99%
“…The variability and complexity of PICA anatomy makes aneurysms appear in unusual locations, and there is great variation in shape and size of the lesions. [40] Extracranial PICA aneurysms are frequently associated with aberrant PICA anatomy; lack of caudal or/and cranial loops is frequently observed, and PICA may cross to the contralateral site[2844] [Table 1]. It seems that hemodynamic stress plays an important role in the formation of distal PICA aneurysms,[15] including those formed outside of the cranium.…”
Section: Discussionmentioning
confidence: 99%
“…[202539] Distal PICA aneurysms are even less common,[1226] and can occur extracranially. Overall, only 22 lesions reported in the literature have been located extracranially,[12359101116171819232837394042434445] and of these, only 11 were distal aneurysms. [29]…”
Section: Introductionmentioning
confidence: 99%